Standardization of the formulation of pisco sour by sensory acceptability - Jordan Suaraz, Oscar (2015)
A standard formulation for pisco sour elaboration was established using Taguchi method; as a result of the combination of two levels (minimum and maximum) for sugar syrup, lemon juice and egg albumen, four formulas were analyzed by sensory test in relation to general acceptability (appearance and flavor).The most significant factor in acceptability (flavor) was the sugar syrup, so it was considered its maximum level corresponding to the best ranked formula. The most acceptable formulation for 100ml of pisco (from quebranta grape), includes 50g of ice cubes, 36ml of sugar syrup, 30ml of lemon juice and 10ml of egg albumen at normalized preparation process.